PENGARUH NPM, ROE, DAN ROI TERHADAP NILAI PERUSAHAAN PADA SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DALAM JII70 PERIODE 2018 - 2022 - Bramasta Dafa, (2023)
This study aims to gain an understanding of the impact of Net Profit Margin (NPM), Return On Equity (ROE), and Return On Investment (ROI) on firm value. The object of research is companies in the telecommunications sector listed on the Jakarta Islamic Index - 70 (JII70). Samples were taken using Purposive Sampling method from six companies in the telecommunications sector listed in JII70 in the period 2018 to 2022. This study uses a quantitative method with a panel data regression analysis approach. The research findings show that partially, NPM has no significant effect on firm value, ROE has a significant effect on firm value, and ROI has a significant effect on firm value. Simultaneously, the three variables have an influence on firm value.